1993
DOI: 10.1111/j.1440-1681.1993.tb01652.x
|View full text |Cite
|
Sign up to set email alerts
|

BLOOD PRESSURE EFFECTS OF THROMBOXANE A2 BLOCKADE IN SPONTANEOUSLY HYPERTENSIVE RATS

Abstract: 1. The effects of CGS 22652, a thromboxane (Tx) A2 synthase inhibitor and TxA2/prostaglandin (PG) H2 receptor antagonist, on blood pressure (BP) were studied in conscious freely moving spontaneously hypertensive rats (SHR). 2. Three groups of 13 male SHR were subcutaneously infused from 5 to 11 weeks of age via osmotic minipumps with CGS 22652 at doses of 5 (SHRa) or 10 (SHRb) mg/kg per 24 h or with the vehicle only (SHRc). A fourth group (SHRd, n = 13) was orally treated from 3 to 11 weeks of age with CGS 226… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…It has been reported that blockage of TXA 2 synthetase induced a significant antihypertensive effect in SHR. 21,22 The antihypertensive effect may be due to improvement of renal function and due to decrease in the pressor effects of TXA 2 and of noradrenaline. In contrast to SHR, the depressor effect is not obtained in hypertensive Dahl rats, although blockage of TXA 2 synthetase ameliorates renal functional and structural lesions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that blockage of TXA 2 synthetase induced a significant antihypertensive effect in SHR. 21,22 The antihypertensive effect may be due to improvement of renal function and due to decrease in the pressor effects of TXA 2 and of noradrenaline. In contrast to SHR, the depressor effect is not obtained in hypertensive Dahl rats, although blockage of TXA 2 synthetase ameliorates renal functional and structural lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Thromboxane A2 elevates BP through several mechanisms, such as salt and water retention, 18 activation of the sympathetic nervous system, 19 enhancement of the vasoconstrictor effects of angiotensin (Ang)II, 20 noradrenaline, 18 endothelin-1, 21 5-hydroxytryptamine and vasopressin. [11][12][13][14][15][16]23 However, some results suggest that TxA2 synthase inhibitors, but not TxA2/PGH2 receptor antagonists, have the ability to lower BP in SHR. [5][6][7][8][9] If TxA2 is profoundly involved in the development of hypertension in SHR, inhibition of TxA2 synthesis or blockade of TxA2/PGH2 receptors could lower BP in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings on the effects of a TxA2 synthase inhibitor and TxA2/PGH2 receptor antagonist on BP in SHR have been conflicting. [11][12][13][14][15][16]23 However, some results suggest that TxA2 synthase inhibitors, but not TxA2/PGH2 receptor antagonists, have the ability to lower BP in SHR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations